Analysis of common bean (Phaseolus vulgaris L.) trade in Cameroon: A trader's perspective of preferred varieties and market traits - Nchanji, Eileen Bogweh; Bella Ngoh, Siri; Toywa, Johnworker; Lutomia, Cosmas Kweyu (Elsevier, 2023)
Common beans contribute towards enhancing food and nutritional security in developing countries. Producing the right varieties entails that the interest of all value chain actors, like traders (wholesalers, retailers, and aggregators), are considered in developing breeding priorities to meet local and export market demand. However, there is little or no information on traders' perspectives regarding the preferred common bean traits and variety; hence, this study sought to fill the gap. This study aimed to analyse common bean trade in Cameroon by focusing on the trader's perspective of preferred varieties and market traits. A market survey was conducted in August 2021. Four regions of Cameroon (Adamawa, Centre, West, and Littoral) were purposively selected based on accessibility, and high concentration of bean traders and are considered the major bean distribution and consumption hubs. A two-stage random sampling was then used to select 175 traders. Data was gathered using a semi-structured questionnaire and analysed descriptively using Excel and STATA 14 software. The results indicated that 80% of bean trade was with Gabon and Congo. The majority of the sampled traders were men, as more men are involved in the bean business. Also, the majority of the traders did not participate in contract farming arrangements. Two market classes of beans were popular: red and white beans. The red beans were popular in the market probably due to good market traits such as affordability, good taste, high yield and early maturity. White bean market class was popular in the export market. Conversely, the black bean market class was the least preferred in the market. The most preferred market traits for improved common beans were good taste and acceptability by buyers. White beans fetched the highest wholesale (1.72 USD) and retail (1.41 USD) prices per kg on the market. Conversely, black beans fetched the lowest wholesale (0.8 USD) and retail (0.75 USD) prices per kg on the market. We recommend that common bean breeders should involve traders as important stakeholders whose market intelligence can be useful in developing improved bean varieties, which are demand-driven. Also, governmental and non-governmental agencies should promote improved common bean varieties to enhance productivity that meets the high demand in local and export markets. Besides, they should promote traders' participation in contract farming arrangements to enhance the steady supply of improved common beans on the market.